Awareness on Scabies among Adults Residing in Rural Areas - A Descriptive Study - Chaudhari, Jyoti; Thomas, Celina; Pati, Pranita; Patil, Snehal; Bhosale, Sonali; Salunke, Triveni; Pathak, Divya (International Journal of Nursing Research, 2024)
Background: Scabies is one of the most common neglected skin diseases seen in developing countries. Awareness of disease and hygienic practices can drastically reduce the incidence and related consequence in later years of life. With this view study is undertaken to assess the awareness of scabies and its prevalence in the rural community of Raigad district. Methodology: A descriptive research design with a total enumeration sample was undertaken for the study. The adults age and/above 20 years, residing in Dhodhani village of Raigad district and willing to participate were chosen for data collection using researcher made pre-validated semi structured interview schedule. A total sample was 48 adults who were able to understand and communicate in local language. Results: Out of 48 participants, 39 participants (81.25%) have heard about scabies. The total awareness score of participants regarding sign and symptoms and consequences of scabies was 47.6%. None of the participants were knowing all sign and symptoms, and consequences of scabies of health and productivity. The total awareness score regarding etiology, predisposing factors and measures for prevention were only 35.4% and about management of scabies the score was 51.6%. The mean awareness score was 44.9%. The survey resulted into finding out of 2 cases of scabies in the community. Conclusion: From this study, researchers concludes that majority (81.25%) participants has heard about scabies, however understanding of scabies as a skin disease, its causes, sign and symptoms, and prevention was inadequate. There is great need for development of consciousness about scabies to protect self.